Emergence of the concept of platelet reactivity monitoring of response to thienopyridines. Issue 15 (5th February 2009) - Bonello, L; De Labriolle, A; Scheinowitz, M; Lemesle, G; Roy, P; Steinberg, D H; Pinto Slottow, T L; Pakala, R; Pichard, A D; Barragan, P; Camoin-Jau, L; Dignat-George, F; et al.
Abstract : Clinical trials have demonstrated the beneficial impact of clopidogrel in preventing major adverse cardiovascular events (MACE), particularly in patients undergoing percutaneous coronary intervention (PCI). The concept of biological clopidogrel resistance emerged with the finding of persistent platelet activation despite clopidogrel therapy in some patients. Further, a link between biological clopidogrel resistance and thrombotic recurrence after PCI was observed and a threshold of platelet reactivity (PR) for thrombotic events was suggested. Consistently, in recent trials, enhanced PR inhibition translated into a reduction in the rate of MACE after PCI. This review aims to present the emergence of the concept of PR monitoring in patients undergoing PCI following recent advances in this field.